First nearly complete genome sequence of porcine bocavirus strain from Malaysia - Lee, Chee Yien; Tan, Chew Yee; Tan, Yi Jing; Wong, Jeffrey Wai Nung; Jacob, Daniel Mohan; Lim, Jia Xin; Ananthan, Gunaselvi; Arshad, Siti Suri; Selvarajah, Gayathri Thevi; Ooi, Peck Toung (Nexus Academic Publishers, 2019)
This paper reports the first nearly complete genome sequence of a Malaysian Porcine bocavirus (PBoV) detected in Malaysia from a porcine organ sample. In Malaysia, both Human bocavirus (HBoV) and PBoV have been reported, at prevalence of 5.6% and 90.9% respectively. Most recently, in 2018, PBoV emerged as a zoonosis when a human case of PBoV-related respiratory infection is reported in a child with history of contact with porcine secretion. With this evidence of human infection with PBoV, considering close contact between humans and pigs in the swine industry, further study of PBoV genetic characterization and epidemiology is warranted. This study attempts to obtain the complete genome sequence of a Malaysian PBoV isolate detected in a pig farm in the state of Selangor. A nearly complete sequence was obtained through primer walking and touchdown PCR method. Based on phylogenetic analysis for the nearly complete genome, the Malaysian PBoV strain is genetically characterized as PBoV G3B, sharing a close relationship with a reference PBoV strain from U.S.A. with 98% homology. This finding may facilitate further epidemiological studies and diagnostic development of PBoV in Malaysia.